Insulin-like growth factor-1 short-period therapy improves Non-Alcoholic Fatty Liver Disease (NAFLD) in obese mice - Daniela C. Andrade; Filipe Jorge Nascimento; Genilza P. de Oliveira; Thiago Freire; Simone N. de Carvalho; Ana Carolina Stumbo; Laís Carvalho; Alessandra A. Thole; Erika Cortez (Brazilian Journal of Health and Biomedical Sciences, 2023)
This study seeks to evaluate Insulin-like Growth Factor 1 (IGF-1) short-period therapy in Non-Alcoholic Fatty Liver Disease (NAFLD) as it relates to western diet-induced obesity. For this purpose, 21-day-old male Swiss mice were divided into a control group (CG, N=8), which was fed a standard diet, and an obese group (GO, N=16), which was fed a western diet, rich in saturated fat and simple carbohydrates, for 12 weeks. In the 11th week, part of the animals in the obese group (N=8) received a daily subcutaneous injection of recombinant human IGF-1 (100µg/kg/day) during seven consecutive days (GO+IGF-1). Biometric and metabolic parameters, intraperitoneal glucose tolerance test (IGTT), quantitative analysis of liver steatosis, quantitative analysis of collagen in liver and expression of immunoperoxidase of alpha-smooth muscle actin (a-SMA) were analyzed. Our data demonstrated that IGF-1 short-term treatment was able to improve obesity-related biometric and metabolic parameters. In addition, it promoted the recovery of liver parenchyma, thereby reducing steatosis and fibrosis, thus demonstrating an important hepatoprotective action.